Management of allergic conjunctivitis: an evaluation of the perceived comfort and therapeutic efficacy of olopatadine 0.2% and azelastine 0.05% from two prospective studies - Epstein, Arthur B (Dove Medical Press, 2009)
PURPOSE: Results from 2 patient-reported outcome studies of allergic conjunctivitis sufferers who used olopatadine 0.2% and azelastine 0.05% are analyzed. METHODS: The PACE (Pataday Allergic Conjunctivitis Evaluation) multi-center, prospective, open-label study examined patient perceptions of olopatadine 0.2% once daily (qd) and previous twice daily (bid) allergic conjunctivitis medications via questionnaire in allergic conjunctivitis sufferers who had previously used bid medication and then initiated olopatadine. A second conjunctival antigen challenge (CAC) study evaluated comfort of 4 allergic conjunctivitis medications. RESULTS: Forty-nine patients from the PACE study (N = 125) with prior azelastine use were examined. Significantly more patients rated themselves “very satisfied” with current olopatadine use compared with past azelastine use on drop comfort (p < 0.0001), speed of relief (p = 0.0004), and overall satisfaction (70% vs 16%, p < 0.0001). Significantly more patients reported olopatadine “very effective” against swelling compared with azelastine (47% vs 8%, p = 0.0404). In the CAC study (N = 36), data from olopatadine (n = 8), azelastine (n = 9) and placebo (N = 36) groups were reported. Olopatadine was rated significantly more comfortable than azelastine upon instillation (p = 0.0223), at 30 seconds (p = 0.0479), and at 1 minute after instillation (p = 0.0240). CONCLUSION: In the reported studies, olopatadine 0.2% qd was more comfortable than azelastine 0.05% and preferred by patients with allergic conjunctivitis by a ratio of 4:1.